Feminisms: Diversity, Difference and Multiplicity in Contemporary Film Cultures, Laura Mulvey and Anna Backman Rogers (eds) (2015). (1st December 2016) - Walsh, Maria
Amsterdam: Amsterdam University Press, 276 pp., ISBN: 9789089646767, p/bk, €39.95